Podstępne wprowadzenie w błąd (kan. 1098 KPK) w opublikowanych orzeczeniach Roty Rzymskiej z lat 2010-2012 - Góralski, Wojciech (Ius Matrimoniale, 2019)
The subject of this study is the jurisprudence of the Roman Rota Court regarding deceptive misleading (canon 1098 CIC) from 2010-2012, contained in Decisione seu sententiae. During this period, the title of marriage annulment was included in twelve judgments; ten of them have been published. The analysis of rotating sentences was presented in the following thematic areas: deceptive misleading as a factor protecting marriage consent; deceptive action; error as a result of deception; the attribute of a person as an object of deceptive action (in genere and in individual judgments); deceptio dolosa prove. Undoubtedly, the jurisprudence of the Roman Rota also provides for the area of ​​deceptive misleading, the appropriate point of reference in the resolution of nullitatis matrimonii cases by church tribunals of lower degrees of jurisdiction.